Historical and Economic Analysis of Scientific Views on the Development of the Agri-Food Market in the Post-Soviet Economic Region - Kuraev Aleksey Nikolayevich; Zhakhov Nikolay Vladimirovich; Krivoshlykov Vladimir Sergeevich; Melnikova Elena Nikolaevna; Belostotskiy Alexey Alexandrovith (Communications of International Proceedings, 2020)
the relevance of scientific research is determined by clearly expressed growing economic imbalances in the world agri-food markets and a more balanced and balanced (without structural distortions and tariff restrictions) agri-food policy within the Eurasian Economic Union. The historical and economic analysis of scientific views on the development of the agri-food market in the post-Soviet region will allow in the future, will serve as the foundation for modeling and designing organizational and economic tools to smooth out market imbalances, which will improve the institutional efficiency of the market (in our case, agri-food), as well as is one of the fundamental issues of the new institutional economy. The conducted historical and economic analysis of scientific views on the development of the agro-food market of the Eurasian Economic Union, a new global union created in the territory of the post-Soviet space, the region made it possible to identify the prevailing fundamental foundations and formed views of scientists on the problem under study.
Keywords: Historical and Economic Analysis; Agro-Food Market; Eurasian Economic Union; Common Economic Space; Economic Security; Food Security.